In situ observation of compressive deformation of an interconnected network of zinc oxide tetrapods. (February 2023) - Veys, Eloise; Makower, Louis; Williamson, Marcus; Saure, Lena M.; Adelung, Rainer; Schütt, Fabian; Pugno, Nicola M.; Marrow, Thomas James
Abstract: Zinc oxide tetrapods have remarkable functional and mechanical properties with potential applications in different fields including nanoelectronic and optoelectronic sensing, functional composites and coatings, as well as energy harvesting and storage. Based on the 3D shape of these microparticles, they can be assembled into highly porous (up to 98%) macroscopic ceramic framework structures that can be utilized as a versatile template for the fabrication of other multi-scaled foam-like materials. Here we investigated the three-dimensional structure of low density interconnected zinc oxide tetrapod networks by high resolution X-ray computed tomography. In situ observations during mechanical loading show inhomogeneous development of anelastic strain (damage) during compression, and homogeneous elastic recovery on unloading. Individual tetrapods are observed to deform by arm rotation to accommodate strain. Graphical abstract: Image, graphical abstract